Lifestyle and nutrition of the Gulf countries students living in the UK - Almughamisi, Manal Amro; Almaski, Ameerah Mohammed Khairi (Journal of medical and pharmaceutical sciences, 2023)
This paper reports findings from a cross-sectional study carried out in May- July 2022 among international students from the Gulf Cooperation Council Countries (GCC) enrolled at British University in the United Kingdom. The study aimed to examine the influence of lifestyle and nutrition and the impact on health among Arab students in the UK in comparison with their home country. In total, 80 students from two countries (Saudi Arabia and Kuwait) participated. Students who perceived dietary change since moving to the UK was 68.9%. The most common reason for dietary changes was time constraints, followed by food availability, food cost and type. A significant change was observed in the consumption of sugary drinks, sweets and/or chocolates, cakes, doughnuts, and frequent eating in restaurants among students after moving to the UK. Duration of walking significantly increased by the students in the UK in comparison to home country. The present study shows that international students from the Gulf countries faces different factors influence their dietary practice. Time constraints, price, availability of the food to be barriers to maintaining usual eating patterns. University hosting international students can alleviate some of these issues experienced by students, for example, by providing information on the location of retailers in the area of the university selling good quality fresh products at a reasonable price.
Keywords: Dietary habits; international students; Lifestyle; nutrition